The Predictive Level of Emotional Intelligence for the Domain-specific Creativity: A Study on Gifted Students - Sahin, Feyzullah; Ozer, Esin; Deniz, Mehmet Engin (TURKISH EDUCATION ASSOC, 2016)
The relationship between intelligence, emotional intelligence and creative thinking skills is complicated, multi-layered and multidimensional. The general purpose of this study is to determine the relationship between emotional intelligence of the students and their domain-specific creativity and the effect of emotional intelligence in predicting domain-specific creativity. Two different high schools were accepted as the study group and the data obtained from 239 gifted students was included into the study. In the study, the Creativity Tests for Kaufman Domains adapted by Sahin (2015b, 2015c) and the Trait Emotional Intelligence Questionnaire Short Form adapted by Deniz, Ozer and Isik (2013) were employed. The results of analysis revealed that the sociality which is one of the sub-dimensions of emotional intelligence was in relation with the entire creativity subdomain and self/everyday creativity subdimension was in relation with the entire emotional intelligence dimensions. Moreover, it was determined that sociability could predict academic creativity, artistic performance and self/everyday creativity whereas the other dimensions failed in doing it.
Keywords: Gifted; Emotional intelligence; Domain-specific creativity; Creative thinking; CONSENSUAL ASSESSMENT TECHNIQUE; GENERAL INTELLIGENCE; DIVERGENT-THINKING; TALENTED STUDENTS; TORRANCE TESTS; PERSONALITY; TRAIT; IDENTIFICATION; ACHIEVEMENT; KNOWLEDGE; Education & Educational Research